Research progress of optical signal processing with orbital angular momentum - Jun LIU; Jian WANG (Tongxin xuebao)
Light beams carrying OAM (orbital angular momentum) exploit the transverse spatial distribution of photons and have helical phase front.In recent years, similar to the WDM (wavelength-division multiplexing) technology, OAM multiplexing technology has attracted widespread interest and made remarkable progress in high-speed and large-capacity optical signal transmission.It is worth noting that, optical signal processing is also the key technology of optical communication systems in addition to optical signal transmission.A complete OAM-based optical communication network system includes both OAM multiplexing transmission along network links and OAM signal processing at network nodes.The research progress of optical signal processing with OAM were reviewed, and different optical signal processing functions with OAM and the various OAM-based optical signal processing technologies in different application scenarios were comprehensively summarized.Meanwhile, the future development trend of optical signal processing with OAM was analyzed and its prospect was discussed.The optical signal processing technologies with OAM improve the OAM-based space-division multiplexing optical communication systems, which is expected to provide solutions for realizing efficient and flexible information management of OAM and addressing the new capacity crunch of optical communications.